PHRASEOLOGICAL EUPHEMISMS IN TADJIK LANGUAGE (Scientific journal of the Fergana State University, 2023)
The article reflects the expansion of the sphere of giving lexemes with euphemistic meaning in Tajik linguistics, ways of expressing the meanings of the main word, their grammatical characteristics and features. The widespread use of euphemistic lexemes in every language is an important feature of the national culture of this nation and people. The great changes taking place in our society have made changes in euphemisms in theory and practice and occupy a special place in accordance with the demand of the time.